Cloning of the gfp (green fluorescent protein) gene downstream of the ldh promoter in a bacteriocin-sensitive strain of Lactobacillus sakei to serve as a reporter strain in bacteriocin studies - Liss, Petronella Francina (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2003.